1992
DOI: 10.1111/j.1365-2796.1992.tb00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin to prevent growth of vegetations and cerebral emboli in infective endocarditis

Abstract: The incidence of stroke on cranial computed tomography (CT) and change in echocardiographic vegetation area was prospectively compared in a preliminary observational study involving nine patients with infective endocarditis randomized to either low-dose aspirin (75 mg d-1, Group I, n = 4) or no aspirin (Group II, n = 5). Two symptomatic cerebral infarcts and one myocardial infarct occurred in the controls, compared to no events in patients on aspirin during a total observation period of 343 d (range 28-49 d). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 14 publications
(7 reference statements)
1
22
1
Order By: Relevance
“…Acetylsalicylic acid (ASA, aspirin) has been used in vitro and in a number of experimental models to reduce vegetation sizes and to mitigate the course of disease (23)(24)(25). Similar effects have also been observed by Kupferwasser et al (26).…”
Section: Importance Of Staphylococcal Attachment and Invasion In Endosupporting
confidence: 53%
“…Acetylsalicylic acid (ASA, aspirin) has been used in vitro and in a number of experimental models to reduce vegetation sizes and to mitigate the course of disease (23)(24)(25). Similar effects have also been observed by Kupferwasser et al (26).…”
Section: Importance Of Staphylococcal Attachment and Invasion In Endosupporting
confidence: 53%
“…Although these observations may be due in part to ASA's direct effect on platelets, it is likely that this agent's effect on prostacyclin and mediators of adherence, such as thrombospondin and fibronection, also contributes to the observed reduction in both bacterial density and vegetation weight. In addition, the reduction in vegetation weight observed with ASA therapy may have other important clinical implications, such as decreasing the incidence of embolic phenomena that are commonly experienced with endocarditis (13). Although many questions remain and other investigations are required to determine the mechanism responsible for our observations, this study provides encouraging data regarding the role of ASA therapy in the treatment of infective endocarditis.…”
Section: Discussionmentioning
confidence: 49%
“…These animal studies prompted two clinical trials of aspirin as adjunctive therapy in the treatment of IE in humans. The first was a small, prospective, observational study of nine patients with IE who were randomly assigned to either lowdose aspirin or no aspirin [22]. This study found two symptomatic cerebral infarcts and one myocardial infarct in the patient group that received no aspirin (n=5) and no embolic events in those who received aspirin (n=4) [22].…”
Section: Introductionmentioning
confidence: 99%
“…The first was a small, prospective, observational study of nine patients with IE who were randomly assigned to either lowdose aspirin or no aspirin [22]. This study found two symptomatic cerebral infarcts and one myocardial infarct in the patient group that received no aspirin (n=5) and no embolic events in those who received aspirin (n=4) [22]. Given the extremely small numbers of patients in this pilot study, the authors rightly suggested further studies were needed to evaluate the role of aspirin in IE [22].…”
Section: Introductionmentioning
confidence: 99%